التجديد في فقه المعاملات المالية: مساراته ومجالاته - عقون, توفيق (جامعة الوادي university of eloued, 2022)
تناولت في هذا البحث المفهوم الصحيح للتجديد في الدين، وهو إحياء معالمه وإعادة الجدة والحيوية التي كان عليها في عهد السلف، ثم أوردت الدلائل الدالة على مشروعيته، من النصوص والقواعد الشرعية، وبعدها أخذت في تحديد المسارات الأساسية للتجديد في المعاملات المالية، وهي ثلاثة: الإحياء، الإلغاء، الإثراء، ثم ختمت بحثي بذكر العديد من المجالات التي يمكن أن يتحقق فيها التجديد من خلال المسارات الثلاثة السابق ذكرها، والهدف من ذلك ضبط التجديد وتفعيله، وفق المعنى الذي يريده الشرع، حتى لا ينحرف عن مساره، وليضمن حضور الفقه الإسلامي في حياة الناس المعاصرة، ومن أهم ما توصل إليه البحث أن التجديد في الدين مطلب شرعي وضرورة يقتضيها الواقع المتغير، حتى يكون الفقه قادراً على مواكبة القضايا التي استجدت في حياة الناس. In this research deals with the correct concept of renewal in religion, It is the revival of its features and the restoration of the vitality that it was in in the first virtuous times, then the evidences of its legitimacy were presented, From the legal texts and rules, after which I set out the basic paths for renewal in financial transactions, which are three:Cancellation, enrichment, and then I concluded my research with many areas in which renewal can be achieved through the three aforementioned paths,The aim is to control and activate the renewal, according to the meaning the meaning intended by the law, so that it does not deviate from its path and to ensures the presence of Islamic jurisprudence in the lives of contemporary people, one of the most important findings of the research is that renewal in religion is a legitimate requirement and a necessity required by the changing reality, so that jurisprudence is able to keep pace with the issues that have emerged in people's lives
مقال
Keywords: التجديد؛ الفقه؛ المعاملات المالية؛ المعاملات المصرفية; renewal; jurisprudence; Financial transactions; banking transactions